2020
DOI: 10.1097/pcc.0000000000002135
|View full text |Cite
|
Sign up to set email alerts
|

Early Enteral Nutrition Is Associated With Improved Clinical Outcomes in Critically Ill Children: A Secondary Analysis of Nutrition Support in the Heart and Lung Failure-Pediatric Insulin Titration Trial

Abstract: Objectives: The impact of early enteral nutrition on clinical outcomes in critically ill children has not been adequately described. We hypothesized that early enteral nutrition is associated with improved clinical outcomes in critically ill children. Design: Secondary analysis of the Heart and Lung Failure-Pediatric Insulin Titration randomized controlled trial. Setting: Thirty-five PICUs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 43 publications
1
24
0
1
Order By: Relevance
“…Pediatric studies have shown benefits of early nutrition, in both mechanically ventilated and non-invasively supported patients [ 16 , 28 ]. In fact, a recently published retrospective study in four European PICUs reached similar conclusions to ours, reporting safety and tolerance of early enteral nutrition in patients managed on NRS [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric studies have shown benefits of early nutrition, in both mechanically ventilated and non-invasively supported patients [ 16 , 28 ]. In fact, a recently published retrospective study in four European PICUs reached similar conclusions to ours, reporting safety and tolerance of early enteral nutrition in patients managed on NRS [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have highlighted the significance of early EN in the critically ill pediatric population including its role in shorter PICU and overall LOS. 11 14 15 16 There does not appear to be a consensus, however, on the definition and recommendation for early EN and has been stated in the past as anywhere from 24 to 48 hours. 8…”
Section: Discussionmentioning
confidence: 99%
“…There are a few studies detailing the benefits of early EN on infection prevention, clinical outcomes, and lower hospital charges in the general critically ill pediatric population. 11 12 However, there is limited data on the safety and feasibility of providing EN to patients admitted with SA receiving respiratory support via NPPV in the form of bilevel positive pressure ventilation (BIPAP). The need to determine feasibility of EN in children with SA on BIPAP is important, and differs from other respiratory failure cases needing the same, because children with SA on BIPAP recover faster and rarely progress to requiring invasive mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…In a UK-wide survey of PICU physicians, nurses and dieticians (4), the top five barriers were: severe fluid restriction (60%), the child being 'too ill' to feed (17%), surgical post-operative orders (17%), nursing staff being slow in starting feeds (7%) and hemodynamic instability (7%). However, despite the paucity of randomized trial evidence to support enteral feeding during critical illness states, a substantial body of observational study evidence exists (16,17,18,19,20) indicating early EN is both feasible and improves clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%